The short stories - Hemingway, Ernest 1899-1961 (New York, NY Scribner, 2003)
"At the age of twenty-two, Ernest Hemingway wrote his first short story, Up in Michigan. Seventeen years and forty-eight titles later, he was the undisputed master of the short-story form and the leading American man of letters. The Short Stories, introduced here with a revealing Más información ... preface by the author, chronicles Hemingway's development as a writer, from his earliest attempts in the chapbook Three Stories and Ten Poems, published in Paris in 1923, to his more mature accomplishments in Winner Take Nothing. Originally published in 1938 along withThe Fifth Column, this collection premiered The Capital of the World and Old Man at the Bridge, which derive from Hemingway's experiences in Spain, as well as The Short Happy Life of Francis Macomber and The Snows of Kilimanjaro, which figure among the finest of Hemingway's short fictions."--Publisher's description.
The short happy life of Francis Macomber -- The capital of the world -- The snows of Kilimanjaro -- Old man at the bridge -- Up in Michigan -- On the quai at Smyrna -- Indian camp -- The doctor and the doctor's wife -- The end of something -- The three-day blow -- The battler -- A very short story -- Soldier's home -- The revolutionist -- Mr. and Mrs. Elliot -- Cat in the rain -- Out of season -- Cross-country snow -- My old man -- Big two-hearted river: part I -- Big two-hearted river: part II -- The undefeated -- In another country -- Hills like white elephants -- The killers -- Che ti dice la patria? -- Fifty grand -- A simple enquiry -- Ten Indians -- A canary for one -- An alpine idyll -- A pursuit race -- Today is Friday -- Banal story -- Now I lay me -- After the storm -- A clean, well-lighted place -- The light of the world -- God rest you merry, gentlemen -- The sea change -- A way you'll never be -- The mother of a queen -- One reader writes -- Homage to Switzerland -- A day's wait -- A natural history of the dead -- Wine of Wyoming -- The gambler, the nun, and the radio -- Fathers and sons.
"The first forty-nine stories with a brief preface by the author."--Cover.